Alterations in the sense of time, space, and body in the mindfulness-trained brain: a neurophenomenologically-guided MEG study - Berkovich-Ohana, Aviva; Dor-Ziderman, Yair; Glicksohn, Joseph; Goldstein, Abraham (Frontiers in Psychology, 2013)
Meditation practice can lead to what have been referred to as 'altered states of consciousness'. One of the phenomenological characteristics of these states is a joint alteration in the sense of time, space and body. Here, we set out to study the unique experiences of alteration in the sense of time and space by collaborating with a select group of 12 long-term Mindfulness meditation practitioners in a neurophenomenological setup, utilizing first-person data to guide the neural analyses. We hypothesized that the underlying neural activity accompanying alterations in the sense of time and space would be related to alterations in bodily processing. The participants were asked to volitionally bring about distinct states of 'Timelessness' (outside time) and 'Spacelessness' (outside space) while their brain activity was recorded by MEG. In order to rule out the involvement of attention, memory or imagination, we used control states of 'Then' (past) and 'There' (another place). MEG sensors evidencing alterations in power values were identified, and the brain regions underlying these changes were estimated via spatial filtering (beamforming). Particularly, we searched for similar neural activity hypothesized to underlie both the state of 'Timelessness' and 'Spacelessness'. The results were mostly confined to the theta band, and showed that: 1) the 'Then' / 'There' overlap yielded activity in regions related to autobiographic memory and imagery (right posterior parietal lobule, right precentral / middle frontal gyrus, bilateral precuneus); 2) 'Timelessness' / 'Spacelessness' conditions overlapped in a different network, related to alterations in the sense of the body (posterior cingulate, right temporoparietal junction, cerebellum); and 3) phenomenologically-guided neural analyses enabled us to dissociate different levels of alterations in the sense of the body. This study illustrates the utility of employing experienced contemplative practitioners within a neurophenomen